RNA Polymerase II-Dependent Transcription Initiated by Selectivity Factor 1: A Central Mechanism Used by MLL Fusion Proteins in Leukemic Transformation - Yokoyama, Akihiko (Frontiers in Genetics, 2019)
In eukaryotes, RNA is polymerized by three distinct RNA polymerases, RNA polymerase I, II, and III (RNAP1, RNAP2, and RNAP3, respectively). The transcriptional machinery that initiates each transcription reaction has been purified and characterized. Selectivity factor 1 (SL1) was identified as the complex responsible for RNAP1 pre-initiation complex formation. However, whether it plays any role in RNAP2-dependent transcription remained unclear. Our group previously found that SL1 specifically associates with AF4 family proteins. AF4 family proteins form the AEP complex with ENL family proteins and the P-TEFb elongation factor. Similar complexes were independently characterized by several different laboratories and are often referred to as super elongation complex. The involvement of AEP in RNAP2-dependent transcription indicates that SL1 must play an important role in RNAP2-dependent transcription. To date, this role of SL1 has not been appreciated. In leukemia, AF4 and ENL family genes are frequently rearranged to form chimeric fusion genes with MLL. The resultant MLL fusion genes produce chimeric MLL fusion proteins comprising MLL and AEP components. The MLL portion functions as a targeting module, which specifically binds chromatin containing di-/tri-methylated Histone H3 lysine 36 and non-methylated CpGs. This type of chromatin is enriched at the promoters of transcriptionally active genes which allows MLL fusion proteins to selectively bind to previously-active/CpG-rich gene promoters. The fusion partner portion, which recruits other AEP components and SL1, is responsible for activation of RNAP2-dependent transcription. Consequently, MLL fusion proteins constitutively activate the transcription of previously-transcribed MLL target genes. Structure/function analysis showed that the ability of MLL fusion proteins to transform hematopoietic progenitors depends on the recruitment of AEP and SL1. Thus, the AEP/SL1-mediated gene activation pathway appears to be the central mechanism of MLL fusion-mediated transcription activation. However, the molecular mechanism by which SL1 activates RNAP2-dependent transcription remains largely unclear. This review aims to cover recent discoveries about the mechanism of transcriptional activation by MLL fusion proteins and to introduce novel roles of SL1 in RNAP2-dependent transcription by discussing how RNAP1 machinery can be involved in RNAP2-dependent gene regulation.